AN ECO-TRANSLATOLOGICAL STUDY ON STUDENTS’ PERCEPTION OF THE TRANSLATION COMPETENCE - Sriyono, Sriyono; Halili, Mohammad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
This study discussed students’ perception of translation competence with eco-translatology approach. It aims at understanding the students' perception of translation competence and adaptation to the translation activities in class.  The eco-translatology model proposed that students be active as the translator; most activities are students-centered.  Students act as a translator in which they benefit from resources around them as in an ecosystem life.  The method in this study is descriptive by identifying the students’ perception of translation competence. Translation competence is often associated with students taking part in translation subjects only as mastering linguistics competence without knowing the basic translation competence principle. Therefore, by applying eco-translatology, the students know that translation is not merely transferring the language unit and meaning from source texts (ST) into target texts (TT). The research results show that students had a better understanding when eco –translatology was applied. They acknowledge that translator competence should be grasped to be a real translator. Besides, it also indicates that students are aware of the importance of translation competence to develop their knowledge.